Safety and efficacy of liraglutide in patients with obesity: A retrospective observational study across glycemic status groups - Durrani, Ayesha; Hazbullah, Nizamud Din; Hussain, Arshad; Arshad, Wardah; Haider, Bushra; Shuaib, Aqsa (International Journal of Pathology, 2025)
Background: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs), such as liraglutide, have demonstrated efficacy in weight reduction and glycemic control. However, comparative data across obese individuals with differing metabolic states non-diabetic (ND), prediabetic (pre-DM), and type 2 diabetes mellitus (T2DM) remain limited, particularly regarding hepatic, lipid, and safety outcomes. This study aimed at evaluating liraglutide’s efficacy in reducing body weight and improving metabolic parameters (HbA1c, lipid profile, liver enzymes) and its safety in obese individuals across these groups.Methods: A prospective study was conducted on 120 obese patients receiving Liraglutide for six months (ND: n=7; pre-DM: n=16; T2DM: n=97). Baseline demographic, anthropometric, and biochemical parameters were recorded. Outcomes assessed at 3 and 6 months included weight, BMI, HbA1c, blood pressure, liver enzymes (ALT, AST), lipid profile, and adverse events. Between-group comparisons were performed using ANCOVA, adjusting for age, disease duration, and baseline metabolic variables.Results: At baseline, patients with T2DM were older and had significantly higher HbA1c, ALT, total cholesterol (TC), and triglycerides (TG) compared with ND and pre-DM groups (p<0.05). Over six months, weight and BMI decreased significantly in all groups, with the greatest mean reduction observed in T2DM (–13.28 ± 8.22 kg), followed by pre-DM (–13.19 ± 9.34 kg), and ND (–6.43 ± 6.53 kg). Higher baseline HbA1c predicted greater weight loss in T2DM and pre-DM (p<0.001). Liraglutide was associated with reductions in ALT and AST across all groups, particularly in those with elevated baseline levels. Lipid improvements were most pronounced in T2DM, with significant reductions in LDL and TG.Conclusion: Liraglutide therapy in obese patients led to significant weight loss and favorable effects on glycemic, hepatic, and lipid parameters across ND, pre-DM, and T2DM groups, supporting the broader role of Liraglutide in obesity and metabolic disease management.